2012
DOI: 10.1039/c2sm25220a
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Brownian motion in crowded fluids

Abstract: Diffusion in crowded fluids, e.g. in the cytoplasm of living cells, has frequently been reported to show anomalous characteristics (socalled 'subdiffusion'). Several random walk models have been proposed to explain these observations, yet so far an experimentally supported decision in favor of one of these models has been lacking. Here, we show that experimentally obtained trajectories in a prototypical crowded fluid show an asphericity that is most consistent with the predictions of fractional Brownian motion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
121
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(129 citation statements)
references
References 30 publications
8
121
0
Order By: Relevance
“…Other than the mechanisms in confined geometries that lead to subdiffusive behaviors (corralled, hop, and cage diffusion, as discussed in Fig. S8), mechanisms in ''unconfined'' geometries, such as continuous time random walk (93)(94)(95), fractional Brownian motion (96,97), and random walk on a fractal structure (98), can also give subdiffusive MSD curves (11,41,99). A sophisticated differentiation decision tree, such as the one proposed by Meroz's group (41), should be established and rigorously tested.…”
Section: Challenges In Molecular Trajectory Analysismentioning
confidence: 99%
“…Other than the mechanisms in confined geometries that lead to subdiffusive behaviors (corralled, hop, and cage diffusion, as discussed in Fig. S8), mechanisms in ''unconfined'' geometries, such as continuous time random walk (93)(94)(95), fractional Brownian motion (96,97), and random walk on a fractal structure (98), can also give subdiffusive MSD curves (11,41,99). A sophisticated differentiation decision tree, such as the one proposed by Meroz's group (41), should be established and rigorously tested.…”
Section: Challenges In Molecular Trajectory Analysismentioning
confidence: 99%
“…Yet explanations as to why differ widely. Using a range of different techniques, Weiss et al 24,53 have established that the anomalous diffusion observed in crowded dextran solutions is an ergodic process (ruling out CTRW), and have proposed that it was consistent with FBM. In another series of FCS studies, Waxham et al 50,51 have argued that the anomalous behaviour observed arose from heterogeneities in the micro-environment experienced by the tracer particles, leading to a discrete distributions of diffusion coefficients.…”
Section: The Anomalous Yet Brownian Motion Of Proteins In Crowded Dementioning
confidence: 99%
“…Other studies in similar systems have also suggested that protein diffusion in crowded marginally entangled polymer solutions deviates from simple Fickian diffusion 15,24,[50][51][52][53] . This, however, remains somewhat controversial, as mobile obstacles are not expected to produce anomalous diffusion 23 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations